An Evolutionary Dynamic Approach to Altruism - Stefano Zamagni; Pier Luigi Sacco (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
After reviewing recent and less recent literature on altruism and selfishness, the paper discusses in detail the isuue of the relevance og altuistic motivations, as opposed to self-interest, in a well grounded theory of rational choice. The main point is that a proper dynamical analysis of the allocative consequences of altruism must focus not only the actual level of altruism that characterizes the economy, but also on the types, keeping in mind that the time evolution of the stock types across the population, It is shown that the model here presented can be used to interpret altruistically – driven phenomena of transation between social conventions.
Keywords: 330